The role of magnesium orotate in the treatment of arrhythmic syndrome in patients with the connective tissue displasias - E. N. Loginova; Yu. V. Moskvina; G. I. Nechaeva; I. V. Druk; A. A. Semenkin; M. I. Shupina; Yu. V. Tereschenko (Лечащий Врач)
Arrhythmic syndrome associated with connective tissue dysplasia (CTD) is one of the leading lesions of the cardiovascular system in young people. The use of magnesium orotate dihydrate during 4 months allowed to restore the sensitivity of adrenoreceptors, as well as to reduce the incidence of heart rhythm disorders in patients with CTD. Thus, in the program of management of patients with cardiac arrhythmias and CTD, it is reasonable to include magnesium preparations, in particular – magnesium orotate dihydrate, which will improve the effectiveness of antiarrhythmic therapy in this category of patients.